Entrepreneurship Creativity and Innovative Business Models - Burger-Helmchen, Thierry (IntechOpen, 2012)
What are the differences between an entrepreneur and a manager? According to Schumpeter, the main difference lies in the entrepreneur's ideas, creativity, and vision of the world. These differences enable him to create new combinations, to change existing business models, and to innovate. Those innovations can take several forms: products, processes, and organizations to name a few. In this book, an array of international researchers take a look at the visions and actions of innovative entrepreneurs to be at the source of new ideas and to foster new relationships between different actors to change the existing business models.